Cloud Network Performance Analysis with Quality of Service (QoS) Implementation Using Cisco Packet Tracer - Harry Fitrian; Akmal Alfadly; Azil Jabari; Mochamad Firmansyah; Rio Pamungkas; Sahmi Padilaturohmah (Penerbit Jurnal Indonesia, 2026)
The rapid adoption of cloud computing demands optimal network stability through Quality of Service (QoS) to manage data traffic in hybrid environments. This study aims to synthesize the effect of QoS on performance metrics (throughput, delay, jitter, packet loss) and evaluate the reliability of Cisco Packet Tracer (CPT) as a design validation tool. Using a qualitative Systematic Literature Review (SLR) approach, the population includes journals from 2021-2025 from IEEE Xplore and ScienceDirect, with a purposive sample of articles with quantitative QoS data on cloud topologies. Instruments include academic databases and thematic synthesis analysis techniques as well as comparative queuing algorithms (FIFO, PQ, WFQ). The results show a QoS trade-off in the form of a minor throughput decrease for superior stability (WFQ: packet drop 12.11 pps, delay 0.066 s), CPT is effective for logic validation but limited in real-world simulations. The conclusion recommends WFQ and hybrid CPT-emulator testing for tight SLAs.